The Determination of Fair Selling Price: an Ethnomethodology Study in PT. Panderman Property Syariah - Sukamto, Wiwid; Triyuwono, Iwan; Ludigdo, Unti (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to reveal the practice of setting the price of sharia property without banks. This study uses an interpretive paradigm with a religious ethnomethodological approach to find ways or methods of setting the price that are believed in a social environment based on justice value in Islam. The data in this study were obtained from observations in the field, documentation and in-depth interviews with people who are related to setting the price at PT Panderman Properti Syariah. Data analysis was performed using equitable indexicality and equitable reflexivity. The results of the study show that there are four ways to determine the selling price, such as; implementing sharia provisions, determining the pricing objectives, calculating costs and determining fair profit, and bidding and contract arrangement mechanisms. Fair selling price is determined by paying attention to the rights of stakeholders, both those that are related to and those not directly related to the company’s operations. Each stakeholder is fulfilled their rights in a balanced manner.